Механізм адміністративно-правового забезпечення мобілізаційної підготовки та мобілізації в Україні - Шевчук, Юрій Андрійович (Академічні візії, 2025)
The content of the article reveals the essence of the implementation of the mechanism of administrative and legal provision of mobilization training and mobilization in Ukraine, its legal regulation, legislative consolidation and managerial influence on the general formation of the main components of the mobilization process. On the basis of legal analysis, the essence of the determinant "administrative and legal support", which plays an important role in the activity of public administration subjects, was investigated. It is noted that despite the widespread use of the concepts of "administrative and legal support" and "legal support", their generally recognized interpretations are blurred and do not correspond to the final definition. On the basis of the legal analysis of sources of legal literature, it is proved that some terminology of the concept of "legal provision" reflects its activity aspect, and therefore has a dynamic character. Another representation of interpretation is characterized by legal support in the statistical aspect. Regardless of the one-sidedness of the above-mentioned definitions, legal provision is both a set of guarantees, which is its static component, and a process - the activity of state authorities to create the conditions necessary for the realization of rights. It is noted that administrative-legal support", in the opinion of the author, can be defined as the administrative-legal basis of the influence of subjects of public-authority powers on social relations in the field of public administration and activities regulated by administrative-legal norms aimed at regulation, creation, improvement and use of this basis for the implementation of the goals and tasks of administrative law. It is outlined that the study of the mechanism of administrative and legal provision of mobilization training and mobilization, as a legal category and a multifaceted phenomenon, occupies a significant place in social relations, because it regulates all spheres of human life. Taking into account the statements of the majority of scientists and practitioners of administrative activity, it has been proven that the Law of Ukraine "On Mobilization Training and Mobilization" dated October 21, 1993 No. 3543-XII, its content does not meet the current urgent needs to ensure the mobilization resource of the country’s security sector . Саме ці причини сприяли до невідкладного прийняття Закону України «Про внесення змін до деяких законодавчих актів України щодо окремих питань проходження військової служби, мобілізації та військового обліку» від 11 квітня 2024 року № 3633-IX. It was determined that the author understands the mechanism of administrative-legal provision of mobilization preparation and mobilization as the purposeful influence of the activities of subjects of public-authority powers on social relations in the field of public administration, regulated by administrative-legal norms using administrative-legal methods and means for the purpose of preparing the national economy, public authorities for timely and organized mobilization and meeting the needs of the state’s defense capability, ensuring the livelihood of the population against possible aggression and in emergency situations.